Micellar liquid chromatographic determination of arbutin and hydroquinone in medicinal plant extracts and commercial cosmetic products - W. Thogchai (2018)
A simple micellar liquid chromatographic (MLC) procedure for simultaneous determination of arbutin and hydroquinone in medicinal plant extracts and commercial cosmetic products was proposed. This method was developed and validated. The chromatographic conditions were also optimized. All analyses were performed at room temperature in an isocratic mode, using a mixture of 1% (v/v) acetonitrile and 0.006 mol L -1 Brij 35 (pH 6.0) as a mobile phase. The flow rate was set at 1.0 mL min -1 . The analytical column was a 150 × 3.9 mm Nova-Pak C-18 column. The effluent from the analytical column was monitored by UV detection at 280 nm. Under the optimum conditions, arbutin and hydroquinone could be determined within a concentration range of 2-50 μg mL -1 of arbutin, and hydroquinone was obtained with the regression equations; y = 0.045x + 0.042 (r 2 = 0.9923) and y = 0.091x + 0.050 (r 2 = 0.9930) respectively. The limits of detection were found to be 0.51 μg mL -1 and 0.37 μg mL -1 for arbutin and hydroquinone respectively. The proposed MLC method was applied for the determination of arbutin and hydroquinone contents in medicinal plant extracts and commercial cosmetic products. This proposed MLC method is thus suitable for routine analysis of arbutin and hydroquinone in the pharmaceutical formulations, cosmetic products and raw medicinal plant extracts. © ICS © 2013 Society of Cosmetic Scientists and the Société Française de Cosmétologie.